Peranan Kurikulum Lokal Berbasis Agama dalam Pembentukan Kepribadian Peserta Didik Madrasah Aliyah: The Role of Religion-Based Local Curriculum in Forming Students’ Personality of Madrasah Aliyah - Harta, Muh (Dirasat Islamiah: Jurnal Kajian Keislaman, 2024)
This study examines the role of the local religion-based curriculum in shaping the personality of the students of Madrasah Aliyah As'adiyah 1 Atapange, Majauleng District, Wajo Regency which is focused on three problems, namely (1) implementation of local content curriculum, (2) the students’ personality, and (3) the role of the local content curriculum in shaping the personality of the students of Madrasah Aliyah As'adiyah 1 Atapange. This type of research is qualitative, data collected through observation, documentation, and interviews. Processing and analyzing data in the form of inductive, deductive, and comparative. The results showed that the implementation of the religion-based local curriculum at Madrasah Aliyah As'adiyah 1 Atapange was carried out by adding subjects namely Qawaid, Balagah, Mantik, Arudy, Usul Fiqh, Usul Tafsir, Usul Hadith, Rasmi science, Tawhid, Tajweed, Barazanji, Imla', Insha', Muthala'ah, Recitations, and Da'wah. The religion-based local curriculum has a significant role in shaping the personality of students at Madrasah Aliyah As'adiyah 1 Atapage.